Right coronary artery anatomy: anatomical and morphometric analysis - Luis Ernesto Ballesteros (Revista Brasileira de Cirurgia Cardiovascular/Brazilian Journal of Cardiovascular Surgery, 2011)
BACKGROUND: It is necessary knowing the large variability of right coronary (RCA) artery specialty for its implications in surgical procedures and clinic events. This variability is usually related to the length, branches quantity, origin and irrigated territories.OBJECTIVE: To evaluate by direct examination the morphologic expression of RCA in Colombian people.METHODS: RCA were measured in 221 fresh hearts by RCA ostium canalization with polyester synthetic resin that was injected in their branches.RESULTS: The caliber of the RCA proximal segment and at the level of the acute angle of the heart was 3.42 ± 0.66 mm and 2.9 ± 0.50 mm, respectively. It ended between crux cordis and the left margin in 75.6% of specimens. Posterior interventricular artery (PIA) reached the inferior third, or the apex, or the anterior interventricular sulcus in 149 (67.4%) cases. Sinoatrial node artery (SNA) originated in the right coronary in 134 (60.6%) cases, 77 (34.9%) from circumflex artery (CxA) and from both in 10 (4.5%). Posterior right diagonal artery (PRDA) was noted in 38 (17.2%) hearts, but only 6% of the sample with long PIA, concomitantly presented the PRDA (P = 0.001). In right dominance SNA were originated from RCA in 54.7% and form CxA in 46.3% (P = 0.06).CONCLUSIONS: Caliber of the RCA and its branches is lesser than the majority of previous studies, while the PRDA frequency is slightly higher than the reported in literature. Clinical and pathological scenarios by these variations should be taken into account: hemodynamic procedures, cardiac surgery and arrhythmias from coronary occlusive disease.